Familial multiple discoid fibromas: unique histological features and therapeutic response to topical rapamycin. (8th July 2013) - Wee, J.S.; Chong, H.; Natkunarajah, J.; Mortimer, P.S.; Moosa, Y.
Summary Familial multiple discoid fibromas is a rare genodermatosis that bears some resemblance to Birt–Hogg–Dubé syndrome but is not associated with mutations in the folliculin (FLCN) gene or systemic manifestations. It is characterized by the development of papules over the face and pinnae early in life. Histological findings are of fibrovascular tumours adjacent to hair follicles without features characteristic of fibrofolliculomas, which have recently been termed discoid fibromas. We present siblings with multiple papules over the face and pinnae that developed in childhood. Histological specimens from both siblings demonstrated discoid fibromas, but with some lesions exhibiting an unusual keloidal‐like pattern with thick hyalinized collagen fibres surrounded by plump spindle and histiocyte‐like cells. FLCN gene mutations were not found. We report on clinical improvement with topical rapamycin solution (1 mg mL−1) applied daily to the face for 4 months. Therapeutic response to topical rapamycin may provide a clue to the underlying genetic basis of this condition.